Challenges in the Implementation of the Distribution of Non-Cash Social Assistance Based on Presidential Regulation Number 63 of 2017 - Erny Rosyanti; Dwian Hartomi Akta Padma Eldo; Alfi Arif Saputro; Arif Zainudin (Universitas Muhammadiyah Ponorogo, 2022)
The distribution of non-cash social assistance until now still has problems that are pretty complicated in its implementation. This study aims to see how Presidential Regulation Number 63 of 2017 regarding the distribution of non-cash social assistance for the community. So that this research is not too broad, the researchers only focus on implementation in 2018. This study uses a qualitative descriptive approach with the object of this research being in the Taman District, Pemalang Regency, Central Java Province by taking samples in Kedungbanjar Village, North Jebed Village, South Jebed Village. The technique of collecting data is using in-depth interviews with stakeholders and the community who receive social assistance. The study results show that the 3 villages have the same tendency in the problems faced when implementing Presidential Regulation number 63 of 2017 concerning non-cash social aid for the village community, namely the assistance that is not on target received by the local community. In addition to the support that was not well-targeted, it turned out that another finding was the problem of communication between the government and the community that did not go well, confusing the community regarding the procedure for distributing this non-cash food aid.